Honor and Violence against Women in Iraqi Kurdistan - Alinia, Minoo; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
This book examines violence against women in the name of honor in Iraqi Kurdistan, taking an intersectional perspective. It reveals the links between destructive, state-sanctioned honor discourse and notions of manhood as they are shaped by a resistance culture dedicated to the struggle against ethnic oppression.
Keywords: Science; Science, general